Interactions within climate policyscapes: a network analysis of the electricity generation space in the United Kingdom, 1956–2022 - Zambianchi, Valeria; Biedenkopf, Katja (Frontiers in Climate, 2024)
The system of policies impacting climate change mitigation is complex. The concept of policy mixes employs a system perspective to understand policies' interactions. We expand this approach to untangle the interactions unfolding within the system of policies affecting climate change mitigation. Against this backdrop, we bring together the concepts of policy mixes and policyscapes by analysing climate policyscapes for electricity generation. Climate policyscapes are populated with both policies supporting climate change mitigation and policies hindering it. We apply this concept to the electricity generation sector. As a complex system, a climate policyscape is greater than the sum of its parts. Unfolding the dynamics within a climate policyscape requires a thorough understanding of the interlinkages among all of its components. We do so by populating the policyscapes between 1956-2022 with the pieces of legislation in the electricity generation space whose policy means affect climate change mitigation. Yet, to date, we have limited conceptual and empirical knowledge on if (and how) policies interact in a system affecting climate change mitigation. This paper contributes to this strand of literature by approaching the concept of policy mixes from a policyscape perspective and analysing the evolution of the UK climate policyscape from 1956 to 2022. Our network analysis of the 2022 climate policyscape reveals that policies hindering climate mitigation remain largely present, which renders the climate policyscape incoherent. We show that policies supporting mitigation are more likely to behave as a group than policies hindering climate mitigation. Climate policies tend to be adopted as packages, whilst fossil policies remain a steady process throughout the history of the UK climate policyscape.